Persepsi Mahasiswa Pendidikan Olahraga terhadap Perkuliahan Daring Selama Pandemi Covid-19 - Ika Yulianingsih; Doby Putro Parlindungan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The aim of the study was to determine the perceptions of sports education students towards online lectures during the Covid-19 pandemic. The method used in this research is descriptive quantitative by examining the perceptions of students in the Sports Education Faculty of Education, University of Muhammadiyah Jakarta. Data collection techniques using surveys through online questionnaires. The number of samples used in the study amounted to 65 students. The results of this study showed the percentage of 92.3% of students agreed with online learning, 6.1% disagreed with and 1.5% disagreed in taking online learning during the Covid-19 pandemic. In conclusion, students agree with the existence of online learning during the Covid-19 pandemic Keywords: Perception, Online Lectures, Covid-19 Pandemic